Contractual Indescendibility: Examining Inheritance of Income-Generating Digital Accounts - Reed, Lars Torleif (Science and Technology Law Review, 2019)
With the rise of user-generated online content, a new form of asset has emerged: income-generating digital accounts (IGDAs), such as YouTube accounts. These accounts can be extremely lucrative financial assets for the account holder. However, due to their contractual nature, IGDAs and their accompanying revenue are difficult—if not impossible—to pass on through normal inheritance. This Article explores the legal framework surrounding inheritance of digital assets, the hurdles to inheritance presented by federal antihacking statutes, and recent efforts to improve fiduciary access to digital assets. I argue that both current laws and proposed reforms fail to resolve adequately the issues surrounding IGDAs, and that legislative reform of digital inheritance law is required. I propose facilitating inheritability through statutorily implied contractual terms.